2002
DOI: 10.1128/aem.68.12.6292-6299.2002
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Multiple Proteobacterial Endosymbionts in the Gills of the Wood-Boring Bivalve Lyrodus pedicellatus (Bivalvia: Teredinidae)

Abstract: Wood-boring bivalves of the family Teredinidae (commonly called shipworms) are known to harbor dense populations of gram-negative bacteria within specialized cells (bacteriocytes) in their gills. These symbionts are thought to provide enzymes, e.g., cellulase and dinitrogenase, which assist the host in utilizing wood as a primary food source. A cellulolytic, dinitrogen-fixing bacterium, Teredinibacter turnerae, has been isolated from the gill tissues of numerous teredinid bivalves and has been proposed to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 37 publications
2
73
0
Order By: Relevance
“…A probe broadly targeting the domain bacteria (21) (EUB338 ; Table S11) was labeled at the 5′ end with Alexa Fluor 594. Tissues were fixed in 4% (wt/vol) paraformaldehyde in seawater, embedded in paraffin, and sectioned as previously described (12). Optimal hybridization conditions were predicted using the mathFISH program (mathfish.cee.wisc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A probe broadly targeting the domain bacteria (21) (EUB338 ; Table S11) was labeled at the 5′ end with Alexa Fluor 594. Tissues were fixed in 4% (wt/vol) paraformaldehyde in seawater, embedded in paraffin, and sectioned as previously described (12). Optimal hybridization conditions were predicted using the mathFISH program (mathfish.cee.wisc.…”
Section: Methodsmentioning
confidence: 99%
“…1D) are found in an internal region of the gill referred to as the gland of Deshayes (11)(12)(13)(14)(15). Culture-independent 16S rRNA gene analyses have shown that the gill endosymbiont community of L. pedicellatus is composed of several endosymbiont types that are closely related to the polysaccharide-degrading gammaproteobacterium Saccharophagus degradans (11,12,16,17) (Fig.…”
mentioning
confidence: 99%
“…Prokaryotic nitrogen fixers are associated with a diversity of eukaryotic hosts in a wide range of habitats, including the well-studied Rhizobium and Bradyrhizobium genera that form root-nodule symbioses with legumes 17 and the actinomycetal Frankia species associated with woody plants 18 . In marine environments, symbiotic nitrogen-fixers are known to be associated with a variety of invertebrates, such as wood-boring bivalves (shipworms) 19 , corals, sponges and sea urchins 20 .…”
mentioning
confidence: 99%
“…However, natural cellulose is difficult to be degraded to glucose owing to its structure and the fact that it is often found in combination with lignin and hemicellulose [3]. Cellulose degradation and utilization are part of the global carbon cycle, with the major degradation power of cellulose in nature derived from cellulases produced by microorganisms [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%